Stroke Risk Factor Profile in an Urban Population: A Community-Based Descriptive Study in Mojo Sub-District, Surabaya, Indonesia - Ilham Ikhtiar; Muhammad Wijdan Rosyich; Muhammad Arief Ardhanu; Dewi Setyaning Bastiana; Dedy Kurniawan; Sita Setyowatie (AKSONA, 2023)
Highlight: The stroke risk of the urban population in Mojo sub-district, Surabaya, was high (more than 10% risk for 36.3% of the population) . The risk factor for stroke is highly prevalent in Indonesia's urban communities, such as Surabaya. The Indonesian version of the Cardiovascular Disease Risk Index chart aids in determining stroke risk factors. The development of a stroke-spesific index chart has been done before but requires validation for the Indonesian population   ABSTRACT Introduction: Stroke is still a major cardiovascular disease in Indonesia. Locally published data regarding stroke risk factors is still rarely reported. This condition complicates the regulation, policy-making, and community empowerment efforts to reduce modifiable stroke risk factors. Thus, a study is necessary to provide an overview of stroke risk factors and risks in cities in Indonesia, such as Surabaya. Objective: This study aimed to describe stroke risk factors in an urban Indonesian community, such as the Mojo sub-district in Surabaya. Methods: This was a descriptive study to describe stroke risk factors like age, gender, history of comorbidities, and history of cardiovascular disease, as well as patient clinical data like neurological symptoms, cardiovascular symptoms, anthropometry, vital signs, simple laboratory values, and cardiovascular risk categorization in the next ten years based on the Cardiovascular Disease Risk Index chart, Indonesian version. Results: In this study, 33 participants were included. Risk factors showed that many participants had histories of active smoking (18.2%), hypertension (45.5%), and diabetes (24.2%). One-third of the participants had a history of dyslipidemia. Based on the risk chart for cardiovascular disease, 36.3% of participants were at >10% risk of developing cardiovascular disease in the next ten years. Conclusion: The risk index of cardiovascular disease in the Mojo sub-district, Surabaya, was still high. A combination of government policies, public awareness improvement, and community empowerment are urgently required to manage these risk factors epidemiologically.